A regulamentação do trabalho doméstico à luz da teoria feminista: da invisibilidade ao reconhecimento - Kamada, Fabiana Larissa (2013)
The paid domestic work, undervalued activity in Brazil, still bears traces of our slave past. Being underpaid, with high rates of informality, developing into long working hours and being endowed with low social protection, domestic work contributes to the feminization of poverty, since the majority of domestic workers are women. This study shows the extent to which sexual division of labor hampers and even manages to derail the achievement of full citizenship of women, perpetuating gender inequality in labor relations, the intended men to productive sphere (public space) and to women reproductive (private area). Because domestic work assignment considered "natural" women, the labor employed therein is overexploited, endowed with little protection, and an urgent need to review the rules of this kind of work, as well as seeking alternatives to configure it as "decent work", a fundamental condition for overcoming poverty, the reduction of social inequalities, ensuring democratic governance and sustainable development. To do so, you must bring the discussion of feminist theory, especially Nancy Fraser, to guide the choices of changes to follow.